ANALISIS EKSPERIMENTAL PENGARUH VARIASI BILAH 2, 4, DAN 6 TURBIN ANGIN SAVONIUS TIPE-L TERHADAP KECEPATAN PUTAR SERTA TORSI PADA KECEPATAN ANGIN RENDAH - Shultoni Mahardika; Ridhani Anita Fajardini; Rahmat Basya Shahrys Tsany; Rizal Indrawan (Politeknik Caltex Riau, 2025)
The utilization of wind energy through vertical axis turbines such as Savonius Type-L is a promising solution for small-scale renewable energy, but the understanding of the effect of blade number variation on its performance is still limited. This study aims to experimentally analyze the performance of the L-type Savonius wind turbine by varying the number of blades (2, 4, and 6) in the wind speed range of 6, 7, and 8 m/s. Tests were conducted using a wind tunnel to measure key parameters such as rotational speed and torque under controlled conditions. The results showed a strong positive correlation, where an increase in wind speed consistently increased the rotational speed and torque across all blade configurations. Specifically, the 4-blade configuration showed the most superior performance, achieving the highest rotational speed and torque compared to other configurations at a wind speed of 8 m/s. This finding confirms that wind speed is a determinant factor in turbine performance and indicates that the 4-blade configuration is the optimal choice to maximize power extraction under the test conditions conducted. Keywords: Savonius, Turbine blade, Torque, Rotational Speed.